2015
DOI: 10.1089/aid.2015.0097
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Low False Recent Rate of Limiting-Antigen Avidity Assay Among Long-Term Infected Subjects from Guangxi, China

Abstract: Assays used for HIV cross-sectional incidence testing can misclassify some individuals with nonrecent HIV infection as recently infected, overestimating HIV incidence. We analyzed the frequency and factors associated with false-recent misclassification on subjects from Quangxi, China known to have long-term infection using the limited antigen-avidity assay (LAg-Avidity). Stored samples from treatment-naive individuals from Guangxi, China were tested using the LAg-Avidity. A total of 362 samples from individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Both the LAg-Avidity EIA and the BED-CEIA PFR were consistent with recent literature. 26,27 The BED-CEIA PFR is the same as was reported from samples collected only from HCMC in southern Vietnam, however, was lower than previously reported in other populations. 2730 The LAg-Avidity EIA was lower than the AxSYM avidity index assay FRR of 2.7% from the HCMC study.…”
Section: Discussionsupporting
confidence: 76%
“…Both the LAg-Avidity EIA and the BED-CEIA PFR were consistent with recent literature. 26,27 The BED-CEIA PFR is the same as was reported from samples collected only from HCMC in southern Vietnam, however, was lower than previously reported in other populations. 2730 The LAg-Avidity EIA was lower than the AxSYM avidity index assay FRR of 2.7% from the HCMC study.…”
Section: Discussionsupporting
confidence: 76%
“…Further, we show how the addition of viral load (VL) information can improve accuracy. Research has shown that VL measurements <1,000 copies/mL are associated with false-recent infections and can identify individuals with viral suppression [ 74 , 75 ]. We used the methods of Shaw et al [ 73 ], Janes et al [ 76 ] and Pepe et al [ 77 ] to obtain estimates for the rFRR and its 95% confidence intervals.…”
Section: 0 Methodsmentioning
confidence: 99%
“…This decrease in antibody concentration may also lead to disappearance of p31 antibodies but seems to have little effect on the overall antibody affinity. Indeed, false recent predictions in patients with late stage disease are rare for the LAg-Avidity EIA [ 7 , 19 , 31 ]. In the decision tree, absence of p31 antibodies in patients identified as recently infected only by BED CEIA is considered indicative for the advanced stage of infection.…”
Section: Discussionmentioning
confidence: 99%